(Invited) Failure Mechanisms in AlGaN/GaN HEMTs Irradiated with 2MeV Protons. (13th April 2015) - Anderson, Travis J; Koehler, Andrew D.; Specht, Petra; Weaver, Brad D; Greenlee, Jordan D; Tadjer, Marko J; Hite, Jennifer K; Mastro, Michael A; Porter, Matthew; Wade, Michael; Dubon, Oscar; Luysberg, Martina; et al.
Abstract : GaN high electron mobility transistors (HEMTs) have shown the potential to be extremely tolerant of the space radiation environment. AlGaN/GaN HEMT structures on three different substrates were exposed to proton irradiation at fluences up to 6x10 14 cm -2, which resulted in a 30% reduction in mobility and saturation current density. Dynamic ON-resistance measurements demonstrated increased degradation by a factor of 10 under off-state quiescent voltage stress conditions. High resolution transmission electron microscopy revealed a radiation-induced void under the gate metallization, indicative of a Kirkendall effect.